2000
DOI: 10.1159/000017515
|View full text |Cite
|
Sign up to set email alerts
|

Depth Psychology-Founded Psychotherapy of Psoriatic Patients – Treatment of a Patient with Chronic Recidivating Psoriasis vulgaris

Abstract: The depth psychology-founded psychotherapy of a 48- year-old woman suffering since childhood from psoriasis is presented. The skin symptoms disappeared almost completely in connection with the resolution of the subject ‘Fulfilling responsibilities versus realization of own wishes and needs’. The psoriasis was again exacerbated in connection with the death of a near relative and renewal of this conflict, which was picked out as a central theme during further treatment. Then the psoriasis improved greatly again … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…Although numerous studies have been performed, the aetiopathogenesis of psoriasis is still not fully understood [Szepietowski et al, 2000;Szepietowski et al, 2001b]. Several internal and external factors could play a role, of which psychological factors are the most important [Fava et al, 1980;Fried et al, 1995;Ginsburg, 1995;Susskind and Mc Guire, 1959;Schmid-Ott, 2000;Zrniç et al, 2001]. Some authors reported a relationship between stress and the onset and exacerbation of psoriasis [Farber and Nall, 1993;Gaston et al, 1987;Gaston et al, 1991].…”
Section: Dokumentation Und Evaluation Der Weiterbildung Original Artimentioning
confidence: 99%
“…Although numerous studies have been performed, the aetiopathogenesis of psoriasis is still not fully understood [Szepietowski et al, 2000;Szepietowski et al, 2001b]. Several internal and external factors could play a role, of which psychological factors are the most important [Fava et al, 1980;Fried et al, 1995;Ginsburg, 1995;Susskind and Mc Guire, 1959;Schmid-Ott, 2000;Zrniç et al, 2001]. Some authors reported a relationship between stress and the onset and exacerbation of psoriasis [Farber and Nall, 1993;Gaston et al, 1987;Gaston et al, 1991].…”
Section: Dokumentation Und Evaluation Der Weiterbildung Original Artimentioning
confidence: 99%
“…The stress experienced due to psoriasis vulgaris varies individually, and not every patient stands to benefit from additional psychosocial therapy in terms of improved skin symptoms. Clinical experience suggests that psychosocial therapy tends to benefit patients with chronic recurrent disease more than those with chronic stationary psoriasis [399].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical experience suggests that psychosocial therapy tends to benefit patients with chronic recurrent disease more than those with chronic stationary psoriasis [399]. The stress experienced due to psoriasis vulgaris varies individually, and not every patient stands to benefit from additional psychosocial therapy in terms of improved skin symptoms.…”
Section: Introductionmentioning
confidence: 99%